Cough in obstructive sleep apnoea. (December 2015) - Chan, Kevin; Ing, Alvin; Birring, Surinder S.
Abstract: Obstructive Sleep Apnoea (OSA) has recently been reported to be a cause of chronic cough. It should be considered when cough remains unexplained following investigations and treatments for common causes. The presence of nocturnal cough, snoring and gastro-oesophageal reflux may be helpful in identifying patients who require further investigation. Daytime somnolence is often absent. Continuous positive airway pressure (CPAP) therapy has been reported to be effective in alleviating cough. Therapy for gastro-oesophageal reflux disease, if present, should be optimised. The mechanism of the association between OSA and cough is not clear, but airway inflammation, gastro-oesophageal reflux disease, increased cough reflex sensitivity and tracheobronchomalacia are possible explanations. Further studies should identify clinical predictors of OSA-cough, establish mechanisms and the optimal therapy.